The Possible Role of Anti-Neu5Gc as an Obstacle in Xenotransplantation - Tector, Alfred Joseph; Mosser, Mathilde; Tector, Matthew; Bach, Jean-Marie (Frontiers in Immunology, 2020)
Seventy to ninety percentage of preformed xenoreactive antibodies in human serum bind to the galactose-α(1,3)-galactose Gal epitope, and the creation of Gal knockout (KO) pigs has eliminated hyperacute rejection as a barrier to xenotransplantation. Now other glycan antigens are barriers to move ahead with xenotransplantation, and the N-glycolyl neuraminic acid, Neu5Gc (or Hanganutziu-Deicher antigen), is also a major pig xenoantigen. Humans have anti-Neu5Gc antibodies. Several data indicate a strong immunogenicity of Neu5Gc in humans that may contribute to an important part in antibody-dependent injury to pig xenografts. Pig islets express Neu5Gc, which reacted with diet-derived human antibodies and mice deleted for Neu5Gc reject pancreatic islets from wild-type counterpart. However, Neu5Gc positive heart were not rejected in Neu5Gc KO mice indicating that the role of Neu5Gc-specific antibodies has to be nuanced and depend of the graft situation parameters (organ/tissue, recipient, implication of other glycan antigens). Recently generated Gal/Neu5Gc KO pigs eliminate the expression of Gal and Neu5Gc, and improve the crossmatch of humans with the pig. This review summarizes the current and recent experimental and (pre)clinical data on the Neu5Gc immunogenicity and emphasize of the potential impact of anti-Neu5Gc antibodies in limiting xenotransplantation in humans.